Monitoring Proses Pengolahan Makanan Moslem Meal Di PT. Aerofood Indonesia, Tangerang, Banten - Anisa Nindyasari; Trias Mahmudiono; Sri Sumarmi (Amerta Nutrition, 2017)
Background: PT. Aerofood Indonesia is an international flight catering company that specializes in Asian, Japanese, Korean, and Western cuisines, as well as pastry and bakery for airline passengers. PT. Aerofood Indonesia also offers special service to its diverse customers by providing special menu, such as moslem meal (MOML). To create MOML menu, there are several procedures that need to be fulfilled, i.e. ingredient and product delivery, storage, preparation production, portioning, packaging, and distribution. Food quality control is needed in each of the procedure to maintain the quality of the beverages. Good quality beverage will prevent physical, chemical, and biological contamination, thus averting the risk of customer health issues. Objectives: This study aimed to gain in-depth knowledge about food production process in in-flight catering, especially in special meal/moslem meal product from delivery, storage, preparation production, portioning, packaging, until the final distribution process to customer inside the airplane. Methods: This study used descriptive method with qualitative approach to achieve the objective. Results: The results showed that quality monitoring for MOML was applied for basic ingredients delivery, storage, preparation, production, portioning, meal tray setup and meal distribution into the airplane. Halal and non halal ingredients were separated by containers and equipments from hot kitchen through portioning area. Monitoring process in each of the production step was focused on critical control point established by PT. Aerofoof Indonesia.Conclusion: Monitoring on moslem meal have been done from food acceptance, storage,through cooking, processing, portioning, meal tray set up and distribution inside the plane.ABSTRAK Latar Belakang: PT. Aerofood Indonesia adalah perusahaan layanan katering penerbangan bertaraf internasional. Jenis makanan yang dibuat seperti Asian cuisine, Japanese/Korean cuisine, Western cuisine, pastry and bakery, dan lain-lain untuk para penumpang pesawat. PT. Aerofood Indonesia membuktikan perhatiannya kepada customer yang memiliki kebutuhan khusus dengan mengadakan menu special meal, salah satunya adalah menu khusus untuk muslim, yaitu Moslem Meal (MOML). Untuk memproduksi menu MOML, membutuhkan proses yang dimulai dari penerimaan bahan, penyimpanan, persiapan, pengolahan, portioning, pengemasan sampai dengan distribusi. Dalam setiap tahapan pengolahan makanan diperlukan monitoring kualitas pangan untuk menjaga kualitas produk makanan dan minuman. Kualitas makanan yang baik akan terhindar dari bahaya kontaminasi makanan baik secara fisik, kimia, dan biologi sehingga tidak menimbulkan gangguan kesehatan.  Tujuan: Tujuan dari penelitian ini adalah untuk mengetahui proses produksi penyelenggaraan makanan di inflight catering, khususnya pada produk special meal (moslem meal) dari penerimaan bahan, penyimpanan, persiapan, pengolahan, portioning, pengemasan hingga pendistribusian makanan ke dalam pesawat di PT. Aerofood Indonesia.Metode: Metode yang digunakan adalah deskriptif dengan pendekatan kualitatif.Hasil: Hasil penelitian meliputi monitoring pada menu moslem meal dilakukan dari penerimaan bahan baku, penyimpanan, persiapan, pengolahan produk, portioning, meal tray set up hingga pendistribusian ke dalam pesawat. Dalam proses pengolahannya, produk halal dengan produk non halal dipisahkan tempat dan equipmentnya dari area hot kitchen hingga di-dishing. Monitoring disetiap area produksi difokuskan pada critical control point yang telah ditetapkan oleh PT. Aerofood Indonesia.Kesimpulan: Monitoring pada menu moslem meal dilakukan dari penerimaan bahan baku, penyimpanan bahan baku, persiapan bahan baku, pengolahan produk, portioning, meal tray set up hingga pendistribusian ke dalam pesawat.